Employee Performance 2.0: Antecedents and Consequences of Gen Z Employees Performance - Wulur, Lies; Mandagi, Deske W. (Program Pascasarjana STIE Amkop Makassar, 2023)
Generation Z (Gen Z) employee performance has become a major topic of focus for firms seeing to optimize their workforce and enhance overall efficiency. However, the dynamic nature of Gen Z employee performance is largely unknown, leaving a notable research gap. This study aims to address this gap by conducting a systematic literature review on the antecedents and consequences of Gen Z employee performance. A comprehensive selection and evaluations of relevant literature was conducted utilizing the Scopus and Web of Science (WOS) databases. A total of 45 research studies were carefully chosen using keywords such as